Standardization of Trigonella foenum-graecum L. Seeds: A Quality by Design Approach - Gaonkar, Vishakha Parab; Hullatti, Kirankumar; Mannur, Vinodh (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: To standardize Trigonella foenum-graecum L. Seeds by developing QbD based HPLC method for identification and quantification of trigonelline in T. foenum graecum L. seeds, along with evaluation of various quality control parameters. Methods: The Analytical Target Profile and Critical Quality Attributes were determined followed by optimization of HPLC method by using 22 factorial design for designing the experiments for selected independent factors. Method Operable Design Region was developed for finding out the optimized chromatographic conditions. Further quality control parameters such as macroscopic and microscopic characters, physicochemical and phytochemical characterization including determination of toxic elements were carried out on the herb. Results: By application of QbD approach the optimized mobile phase was identified as water with 0.01% Hydrochloric acid and Methanol in the ratio of 70:30, with the flow rate of 1 mL/ min and UV detection at 263 nm. The linear model was established in the range of 2-10μg/mL with R2 value 0.998. The retention time of Trigonelline was found to be 2.877 min and the amount of Trigonelline in T. foenum-graecum L. Seeds was found to be 0.58%. The inter-day and intra-day precision were less than 2%, with accuracies between 96.6-110% of the true values. The quality control parameters showed the results within specified limits and the seeds showed absence of toxic elements in it. Conclusion: From the above finding we can conclude that the application of QbD approach for standardization of herbal drug can serve as an important tool for development of herbal drugs with desired quality.
Keywords: Quality by Design; Trigonella foenum-graecum L; Trigonelline; Standardization; HPLC